2016
DOI: 10.5539/gjhs.v8n11p36
|View full text |Cite
|
Sign up to set email alerts
|

Risk Management of Osteoporosis in Postmenopausal Women; A Study of Women In a Teaching Hospital

Abstract: Background: Postmenopausal females are susceptible to osteoporosis due to clinical manifestations. It not only causes morbidity; but, is considered to strikingly decline quality of life among patients. Among different developing regions, the prevalence rate of osteoporosis among postmenopausal women is alarming in the face of poor management and awareness about its risk factors. Aim:The aim of this study was to investigate the incidence of osteoporosis and its known risk factors among postmenopausal women appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The surface of ovarian tissue granulosa cells also express the MT receptor, which indicates that MT can directly regulate ovarian function through a variety of ways. Findings have shown that in many patients with POF, ROS participate in normal follicular development at each physiological stage including: Folliculogenesis and atresia, ovulation, oocyte maturation, and corpus luteum formation (10). MT and its metabolites are considered to be potent antioxidants and free radical scavengers which prevent POF.…”
Section: Discussionmentioning
confidence: 99%
“…The surface of ovarian tissue granulosa cells also express the MT receptor, which indicates that MT can directly regulate ovarian function through a variety of ways. Findings have shown that in many patients with POF, ROS participate in normal follicular development at each physiological stage including: Folliculogenesis and atresia, ovulation, oocyte maturation, and corpus luteum formation (10). MT and its metabolites are considered to be potent antioxidants and free radical scavengers which prevent POF.…”
Section: Discussionmentioning
confidence: 99%
“…13 In 2003, Cheng S et al in their study found that BMD was significantly higher in non-hysterectomised women when compared with hysterectomised women with a p value of 0.001. 14 Gopinath RV et al in their study found that BMD in nonhysterectomised women was 753.36±176.2 g/cm 2 compared to 973.2±108.28 g/cm 2 . It showed significant higher BMD in non-hysterectomised group with a p value of <0.05.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to increased bone fragility and a significantly higher risk of fractures [1,2] . Measuring bone mineral density (BMD) is crucial for early detection of osteoporosis, enabling prompt implementation of effective preventative and therapeutic interventions [3][4][5] . The Human Genome Project is anticipated to uncover early signals of vulnerability to complex diseases using genetic data.…”
Section: Introductionmentioning
confidence: 99%